The Obstacles experienced by Schools in Shaping Religious and Disciplinary Characters in Senior High School Students - Rima Irmayanti (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
The problems of family life are increasingly complex in line with the spirit of changing times and the paradigm of thinking of certain individuals and communities towards the nature or essence of marriage. the purpose of this study is to determine the strategies of single-parent women in meeting children's educational needs. Researchers used descriptive qualitative research methods. The location of this research was Desa Pasanggrahan, Kab. Tangerang. The process of collecting data through a series of observations and in-depth interviews. The researcher used data triangulation and informant review methods in assessing data validity. The research data were analyzed through (1) data collection, (2) data presentation, (3) data reduction, and (4) conclusion drawing. The results showed that the behavior of single-parent women in Pasanggrahan Village, Tangerang Regency in obtaining the fulfillment of household needs and children's education is based on different backgrounds for certain reasons. The conclusion of the research found that the strategy of single-parent women in Pasanggrahan Village in managing their household funds separates which ones are most needed for primary needs to which ones are only used as secondary and tertiary needs.